A tin / hard carbon composite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202410019508.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-05
AI Technical Summary
然而,使用锡作为阳极有两个主要缺点,即循环能力差和库伦效率低,其短寿命周期主要是由于锡在充放电循环过程中大的体积变化引起的
[0038]本发明通过对锡/硬碳复合材料的结构设计,得到若干个单原子锡负载的中空碳球嵌套的复合材料,增强了材料对钠离子的吸附,同时原子状态下分散的锡和中空结构的碳球可显著缓解材料体积膨胀,增强材料的结构稳定性,有效改善材料的循环性能;同时,若干个中空碳球嵌套的内部结构具有更多的反应活性位点,有利于提高材料克容量和首效等电化学性能。本发明的制备方法简单、有效,有利于工业化生产。
Smart Images

Figure CN117673328B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery anode materials technology, and in particular to a tin / hard carbon composite material and its preparation method and application. Background Technology
[0002] With the introduction of dual-carbon goals and the vigorous development of new energy electric vehicles and clean energy, the energy storage field has broad prospects. Currently, lithium-ion batteries hold a core position in the energy market; however, due to the limited availability of lithium resources, uneven geographical distribution, and high cost, they are not suitable for large-scale energy storage applications. Sodium, belonging to the same group as lithium, not only possesses similar physicochemical properties and energy storage mechanisms, but also boasts advantages such as high global abundance, low extraction difficulty, and low cost. Therefore, sodium-ion batteries have a very broad application prospect in large-scale energy storage.
[0003] Sodium is abundant and exhibits a relatively low redox potential, making sodium-ion batteries an important candidate for future lithium-ion batteries. The growing research interest in sodium-ion batteries has accelerated the search for suitable anode materials; elements such as tin, antimony, and lead are suitable for use as anode materials. Among these materials, tin is a promising candidate due to its large theoretical capacity (847 mAh / g). However, using tin as an anode has two main drawbacks: poor cycle life and low coulombic efficiency. Its short lifespan is mainly due to the large volume change of tin during charge-discharge cycles. Summary of the Invention
[0004] To address the aforementioned issues, this invention designs a tin / hard carbon composite material with a nested structure of several hollow carbon spheres and loads single-atom tin onto these spheres. The resulting tin / hard carbon composite material exhibits good structural stability and numerous reactive sites, thereby demonstrating excellent electrochemical performance, including superior cycle performance, specific capacity, and first-efficiency.
[0005] This invention is achieved through the following method:
[0006] In one aspect, the present invention provides a tin / hard carbon composite material, wherein the tin / hard carbon composite material is a nested structure of several hollow spheres, wherein the hollow spheres are composed of single-atom tin distributed on the carbon skeleton of the hollow carbon spheres.
[0007] In one embodiment of the present invention, a single atom of tin is bonded to a hollow carbon sphere by a Sn-C bond.
[0008] In one embodiment of the present invention, tin accounts for 8 wt% to 15 wt% of the tin / hard carbon composite material.
[0009] Another aspect of the present invention provides a method for preparing a tin / hard carbon composite material, comprising the following steps:
[0010] (1) Mix aminophenol, formaldehyde solution, alkaline catalyst and tin salt solution evenly, react to obtain the first mixed solution, add acetone solution to dissolve the soluble matter, filter and dry to obtain tin-loaded hard carbon precursor.
[0011] (2) Under an inert gas atmosphere, the tin-loaded hard carbon precursor is calcined to obtain hollow carbon spheres loaded with single-atom tin.
[0012] (3) Preparation of tin-loaded hard carbon precursor on hollow carbon spheres loaded with tin atoms: Take hollow carbon spheres loaded with tin atoms, aminophenol, formaldehyde solution, alkaline catalyst and tin salt solution, mix them evenly, react to obtain a second mixed solution, add acetone solution to dissolve the soluble matter, filter and dry to obtain the product.
[0013] (4) The product is calcined in an inert gas atmosphere to obtain the tin / hard carbon composite material.
[0014] In one embodiment of the present invention, in step (1), the aminophenol is selected from one or more of o-aminophenol, m-aminophenol, and p-aminophenol, the concentration of the formaldehyde solution is 1 to 1.1 g / mL, and the molar ratio of aminophenol to formaldehyde is 1:2 to 1:4.
[0015] In one embodiment of the present invention, in step (1), the alkaline catalyst is an ammonia solution with a concentration of 10-15 mol / L.
[0016] In one embodiment of the present invention, in step (1), the volume ratio of the ammonia solution to the tin salt solution is 3 to 5:50.
[0017] In one embodiment of the present invention, in step (1), the tin salt in the tin salt solution is selected from one or more of stannous chloride, stannous fluoride, and stannous iodide, and the concentration of the tin salt solution is 0.05 to 0.1 mol / L.
[0018] In one embodiment of the present invention, in step (1), the mass ratio of the aminophenol to the tin salt in the tin salt solution is 1-1.3:0.05-0.15.
[0019] In one embodiment of the present invention, in step (1), the reaction temperature is room temperature and the time is 0.5 to 1 hour.
[0020] In one embodiment of the present invention, in step (1), the volume ratio of water to acetone in the acetone solution is 1:1.
[0021] In one embodiment of the present invention, in step (1), the drying temperature is 70-80°C.
[0022] In one embodiment of the present invention, in step (2), the inert gas is selected from one or more of nitrogen, argon, and helium; the inert gas flow rate is 40-80 mL / min.
[0023] In one embodiment of the present invention, in step (2), the heating rate of the calcination treatment is 0.5 to 5 °C / min, the temperature is 600 to 800 °C, and the time is 6 to 8 h.
[0024] In one embodiment of the present invention, in step (3), the aminophenol is selected from one or more of o-aminophenol, m-aminophenol, and p-aminophenol, the concentration of the formaldehyde solution is 1.09 g / mL, and the molar ratio of aminophenol to formaldehyde is 1:2 to 1:4.
[0025] In one embodiment of the present invention, in step (3), the alkaline catalyst is an ammonia solution with a concentration of 10-15 mol / L.
[0026] In one embodiment of the present invention, in step (3), the volume ratio of the ammonia solution to the tin salt solution is 3 to 5:50.
[0027] In one embodiment of the present invention, in step (3), the tin salt in the tin salt solution is selected from one or more of stannous chloride, stannous fluoride, and stannous iodide, and the concentration of the tin salt solution is 0.05 to 0.1 mol / L.
[0028] In one embodiment of the present invention, in step (3), the mass ratio of the aminophenol to the tin salt in the tin salt solution is 1-1.3:0.05-0.15.
[0029] In one embodiment of the present invention, in step (3), the volume-to-mass ratio of the tin salt solution to the hollow carbon sphere loaded with uniatomic tin is 50 ml: 1-5 g.
[0030] In one embodiment of the present invention, in step (3), the reaction temperature is room temperature and the time is 0.5 to 1 hour.
[0031] In one embodiment of the present invention, in step (3), the volume ratio of water to acetone in the acetone solution is 1:1.
[0032] In one embodiment of the present invention, in step (3), the drying temperature is 70-80°C.
[0033] In one embodiment of the present invention, in step (4), the inert gas is selected from one or more of nitrogen, argon, and helium; the inert gas flow rate is 40-80 mL / min.
[0034] In one embodiment of the present invention, in step (4), the heating rate of the calcination treatment is 0.5 to 5 °C / min, the temperature is 600 to 800 °C, and the time is 6 to 8 h.
[0035] A third aspect of the present invention provides a negative electrode sheet comprising the above-described tin / hard carbon composite material.
[0036] A fourth aspect of the present invention provides a secondary battery comprising the aforementioned negative electrode sheet.
[0037] The technical solution of the present invention has the following advantages compared with the prior art:
[0038] This invention, through structural design of a tin / hard carbon composite material, yields a composite material consisting of several nested hollow carbon spheres supported by single-atom tin. This enhances the adsorption of sodium ions, while the atomically dispersed tin and hollow carbon spheres significantly alleviate volume expansion, improve structural stability, and effectively enhance cycling performance. Furthermore, the nested internal structure of the hollow carbon spheres provides more reactive sites, which is beneficial for improving the material's specific capacity and first-efficiency electrochemical performance. The preparation method of this invention is simple, effective, and conducive to industrial production. Attached Figure Description
[0039] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings.
[0040] Figure 1 Characterization diagram of the multi-shell single-atom Sn / HCS hollow spherical sodium-ion battery anode composite material in Example 1: Figure 1 (a) is a SEM image; Figure 1 (b) is the HAADF-STEM image; Figure 1 (c) is a TEM image. Detailed Implementation
[0041] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0042] The compositions, mixtures, systems, methods, and processes of the claimed invention are intended to include variations and adaptations developed using information derived from the embodiments described herein. Adaptations and / or variations of the compositions, mixtures, systems, methods, and processes described herein can be made by those skilled in the art.
[0043] It should be understood that the order of the steps or the order in which specific actions are performed is irrelevant, as long as the invention remains operational. Moreover, two or more steps can be performed simultaneously.
[0044] Extensive research is underway to improve battery lifespan. In recent years, single-atom composite materials have been developed, exhibiting remarkable performance in storage due to their high atomic utilization and controllable active sites. Single-atom composite materials can enhance electrochemical performance by improving diffusion kinetics and enriching the active sites in alkali metal ion batteries. Simultaneously, the active centers of single-atom composite materials exhibit stable storage behavior without significant volume expansion.
[0045] Therefore, combining the excellent structural stability of nanostructured carbon materials, the high conductivity and high capacity of tin, and the stability of single atoms to construct single-atom carbon-based composite materials can effectively improve the overall electrochemical performance of the electrode. Simultaneously, the stable structure can alleviate the stress released by material deformation during charging and discharging. Thus, achieving the fabrication of a simple and efficient electrode through a straightforward experimental method is of great significance for improving the electrochemical performance of sodium-ion battery anode materials.
[0046] An embodiment of the present invention provides a method for preparing a tin / hard carbon composite material, comprising the following steps:
[0047] (1) Mix aminophenol, formaldehyde solution, alkaline catalyst and tin salt solution evenly, react to obtain the first mixed solution, add acetone solution to dissolve the soluble matter, filter and dry to obtain tin-loaded hard carbon precursor.
[0048] (2) Under an inert gas atmosphere, the tin-loaded hard carbon precursor is calcined to obtain hollow carbon spheres loaded with single-atom tin.
[0049] (3) Preparation of tin-loaded hard carbon precursor on hollow carbon spheres loaded with tin atoms: Take hollow carbon spheres loaded with tin atoms, aminophenol, formaldehyde solution, alkaline catalyst and tin salt solution, mix them evenly, react to obtain a second mixed solution, add acetone solution to dissolve the soluble matter, filter and dry to obtain the product.
[0050] (4) The product is calcined in an inert gas atmosphere to obtain the tin / hard carbon composite material.
[0051] The mechanism of the preparation method of this invention is as follows: Under alkaline conditions, phenols and excess aldehydes react to form spherical phenolic resin. After adding an organic solvent, the cured spherical phenolic resin is insoluble in the organic solvent, while unreacted aldehydes dissolve in the organic solvent (such as acetone solution), thus forming a hollow structure within the spherical phenolic resin. After calcination, hollow carbon spheres are formed. A tin salt solution is added to a mixed solution containing phenols and aldehydes. During the polymerization of the phenolic resin, tin ions polymerize with the O atoms in the phenols / aldehydes due to electrostatic interactions, forming Sn-C and Sn-O bonds during calcination, thus forming hollow carbon spheres loaded with uniatomic tin. After mixing the phenol, aldehyde, and tin salt solutions containing the uniatomic tin-loaded hollow carbon spheres, a spherical phenolic resin is formed through reaction, unreacted aldehydes are dissolved and removed, and after calcination, a tin / hard carbon composite material with a nested hollow sphere structure is formed.
[0052] In a specific embodiment of the present invention, in step (1), the aminophenol is selected from one or more of o-aminophenol, m-aminophenol, and p-aminophenol, the concentration of the formaldehyde solution is 1-1.1 g / mL, and the molar ratio of aminophenol to formaldehyde is 1:2-1:4. Further, the molar ratio of aminophenol to formaldehyde can be 1:2, 1:3, or 1:4. It should be noted that the concentration of the formaldehyde solution is not limited, as long as excess formaldehyde is added to allow the aminophenol and formaldehyde to react and form spherical phenolic resin. If too much formaldehyde is added and it does not participate in the reaction, it will result in material waste and increased costs; if too little formaldehyde is added, the residual formaldehyde will be insufficient, which is not conducive to forming a hollow spherical carbon structure. Therefore, this application preferably uses a molar ratio of aminophenol to formaldehyde of 1:2-1:4.
[0053] In a specific embodiment of the present invention, in step (1), the alkaline catalyst is an ammonia solution with a concentration of 10–15 mol / L. Further, the concentration of the ammonia solution can be 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, or 15 mol / L. The alkaline catalyst provides an alkaline environment for the reaction of aminophenol and formaldehyde. Therefore, the alkaline catalyst can be any alkaline substance, such as ammonia, sodium carbonate, or sodium hydroxide.
[0054] In a specific embodiment of the present invention, in step (1), the volume ratio of the ammonia solution to the tin salt solution is 3 to 5:50. Further, the volume ratio of the ammonia solution to the tin salt solution can be 3:50, 4:50, or 5:50, etc.
[0055] In a specific embodiment of the present invention, in step (1), the tin salt in the tin salt solution is selected from one or more of stannous chloride, stannous fluoride, and stannous iodide, and the concentration of the tin salt solution is 0.05–0.1 mol / L. Further, the tin salt is selected from divalent tin salts, and the concentration of the tin salt solution can be 0.05 mol / L, 0.08 mol / L, or 0.1 mol / L.
[0056] In a specific embodiment of the present invention, in step (1), the mass ratio of aminophenol to tin salt in the tin salt solution is 1–1.3:0.05–0.15. Further, the mass ratio of aminophenol to tin salt in the tin salt solution can be 1–1.1:0.05–0.1, 1.1–1.2:0.05–0.1, 1.2–1.3:0.05–0.1, 1–1.1:0.1–0.15, 1.1–1.2:0.1–0.15, or 1.2–1.3:0.1–0.15. An appropriate amount of tin salt solution can be added according to the concentration of the tin salt solution. If the amount of tin salt added is too small, the tin loading in the tin / hard carbon composite material will be insufficient, and the specific capacity of the material will be reduced. If the amount of tin salt added is too large, the tin cannot be fully loaded onto the hollow carbon spheres, which will result in waste of raw materials on the one hand, and excessive tin loading on the hollow carbon spheres on the other hand, resulting in low material cycle performance and low first efficiency.
[0057] In a specific embodiment of the present invention, in step (1), the reaction temperature is room temperature and the time is 0.5 to 1 hour. Under alkaline conditions, aminophenol and formaldehyde will undergo a series of reactions to form spherical phenolic resin.
[0058] In a specific embodiment of the present invention, in step (1), the volume ratio of water to acetone in the acetone solution is 1:1. The acetone solution is used to wash away excess formaldehyde, which is beneficial for the subsequent calcination process to form hollow carbon spheres.
[0059] In a specific embodiment of the present invention, in step (1), the drying temperature is 70-80°C.
[0060] In a specific embodiment of the present invention, in step (2), the inert gas is selected from one or more of nitrogen, argon, and helium; the inert gas flow rate is 40-80 mL / min.
[0061] In a specific embodiment of the present invention, in step (2), the heating rate of the calcination treatment is 0.5–5 °C / min, the temperature is 600–800 °C, and the time is 6–8 h. Further, the heating rate of the calcination treatment can be 0.5 °C / min, 1 °C / min, 1.5 °C / min, 2 °C / min, 2.5 °C / min, 3 °C / min, 3.5 °C / min, 4 °C / min, 4.5 °C / min, or 5 °C / min; the calcination temperature can be 600 °C, 650 °C, 700 °C, 750 °C, or 800 °C; and the calcination time can be 6 h, 6.5 h, 7 h, 7.5 h, or 8 h. The calcination temperature and time affect the properties of hard carbon (such as carbon interlayer spacing, specific surface area, closed-cell volume fraction, etc.) and tin loading. Due to the inconsistent structures of hard carbon precursors, the calcination processes also differ. The calcination temperature and time of this invention are preferred solutions under the preparation conditions. Those skilled in the art can optimize and adjust them according to the changes in parameters affecting the structure of hard carbon precursors, such as the amount of raw materials added, to meet the required material properties.
[0062] In a specific embodiment of the present invention, in step (3), the aminophenol is selected from one or more of o-aminophenol, m-aminophenol, and p-aminophenol, the concentration of the formaldehyde solution is 1-1.1 g / mL, and the molar ratio of aminophenol to formaldehyde is 1:2-1:4. Further, the molar ratio of aminophenol to formaldehyde can be 1:2, 1:3, or 1:4. It should be noted that the concentration of the formaldehyde solution is not limited, as long as excess formaldehyde is added to allow the aminophenol and formaldehyde to react and form spherical phenolic resin. If too much formaldehyde is added and it does not participate in the reaction, it will result in material waste and increased costs; if too little formaldehyde is added, the residual formaldehyde will be insufficient, which is not conducive to forming a hollow spherical carbon structure. Therefore, this application preferably uses a molar ratio of aminophenol to formaldehyde of 1:2-1:4.
[0063] In a specific embodiment of the present invention, in step (3), the alkaline catalyst is an ammonia solution with a concentration of 10–15 mol / L. Further, the concentration of the ammonia solution can be 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, or 15 mol / L. The alkaline catalyst provides an alkaline environment for the reaction of aminophenol and formaldehyde. Therefore, the alkaline catalyst can be any alkaline substance, such as ammonia, sodium carbonate, or sodium hydroxide.
[0064] In a specific embodiment of the present invention, in step (3), the volume ratio of the ammonia solution to the tin salt solution is 3 to 5:50. Further, the volume ratio of the ammonia solution to the tin salt solution can be 3:50, 4:50, or 5:50, etc.
[0065] In a specific embodiment of the present invention, in step (3), the tin salt in the tin salt solution is selected from one or more of stannous chloride, stannous fluoride, and stannous iodide, and the concentration of the tin salt solution is 0.05–0.1 mol / L. Further, the tin salt is selected from divalent tin salts, and the concentration of the tin salt solution can be 0.05 mol / L, 0.08 mol / L, or 0.1 mol / L.
[0066] In a specific embodiment of the present invention, in step (3), the mass ratio of aminophenol to tin salt in the tin salt solution is 1–1.3:0.05–0.15. Further, the mass ratio of aminophenol to tin salt in the tin salt solution can be 1–1.1:0.05–0.1, 1.1–1.2:0.05–0.1, 1.2–1.3:0.05–0.1, 1–1.1:0.1–0.15, 1.1–1.2:0.1–0.15, or 1.2–1.3:0.1–0.15. An appropriate amount of tin salt solution can be added according to the concentration of the tin salt solution. If the amount of tin salt added is too small, the tin loading in the tin / hard carbon composite material will be insufficient, and the specific capacity of the material will be reduced. If the amount of tin salt added is too large, the tin cannot be fully loaded onto the hollow carbon spheres, which will result in waste of raw materials on the one hand, and excessive tin loading on the hollow carbon spheres on the other hand, resulting in low material cycle performance and low first efficiency.
[0067] In a specific embodiment of the present invention, in step (3), the volume-to-mass ratio of the tin salt solution to the hollow carbon spheres loaded with tin atoms is 50 ml: 1-5 g. Further, the volume-to-mass ratio of the tin salt solution to the hollow carbon spheres loaded with tin atoms can be 50 ml: 1 g, 50 ml: 2 g, 50 ml: 3 g, 50 ml: 4 g, or 50 ml: 5 g. If the amount of hollow carbon spheres loaded with tin atoms is too large, the tin loading in the tin / hard carbon composite material will be insufficient, reducing the material's specific capacity. If the amount of hollow carbon spheres loaded with tin atoms is too small, it will result in raw material waste, and on the other hand, excessive tin loading will lead to low material cycle performance and low first-time efficiency.
[0068] In a specific embodiment of the present invention, in step (3), the reaction temperature is room temperature and the time is 0.5 to 1 hour. Under alkaline conditions, aminophenol and formaldehyde will undergo a series of reactions to form spherical phenolic resin.
[0069] In a specific embodiment of the present invention, in step (3), the volume ratio of water to acetone in the acetone solution is 1:1. The acetone solution is used to wash away excess formaldehyde, which is beneficial for the subsequent calcination process to form a hollow structure, thereby creating a certain gap between the hollow carbon spheres inside.
[0070] In a specific embodiment of the present invention, in step (3), the drying temperature is 70-80°C.
[0071] In a specific embodiment of the present invention, in step (4), the inert gas is selected from one or more of nitrogen, argon, and helium; the inert gas flow rate is 40-80 mL / min.
[0072] In a specific embodiment of the present invention, in step (4), the heating rate of the calcination treatment is 0.5–5 °C / min, the temperature is 600–800 °C, and the time is 6–8 h. Further, the heating rate of the calcination treatment can be 0.5 °C / min, 1 °C / min, 1.5 °C / min, 2 °C / min, 2.5 °C / min, 3 °C / min, 3.5 °C / min, 4 °C / min, 4.5 °C / min, or 5 °C / min; the calcination temperature can be 600 °C, 650 °C, 700 °C, 750 °C, or 800 °C; and the calcination time can be 6 h, 6.5 h, 7 h, 7.5 h, or 8 h. The calcination temperature and time affect the hard carbon properties (such as carbon interlayer spacing, specific surface area, closed-cell volume fraction, etc.) and tin loading. Due to the inconsistent structures of hard carbon precursors, the calcination processes also differ. The calcination temperature and time of this invention are preferred solutions under the preparation conditions. Those skilled in the art can optimize and adjust them according to the changes in parameters affecting the structure of hard carbon precursors, such as the amount of raw materials added, to meet the required material properties.
[0073] Embodiments of the present invention also provide a tin / hard carbon composite material, wherein the tin / hard carbon composite material has a nested structure of several hollow spheres, the hollow spheres being composed of single-atom tin distributed on the carbon skeleton of the hollow carbon spheres. Preferably, the hollow spheres are composed of single-atom tin uniformly distributed on the carbon skeleton of the hollow carbon spheres. When the single-atom tin is in an agglomerated distribution state, it is prone to expansion and deformation, thereby leading to a decrease in cycle performance. The nested structure in the tin / hard carbon composite material refers to a structure composed of multiple hollow spheres of different sizes nested one inside the other.
[0074] In a specific embodiment of the present invention, the tin / hard carbon composite material is composed of two or three nested hollow spheres.
[0075] In a specific embodiment of the present invention, monatomic tin is bonded to hollow carbon spheres by Sn-C bonds.
[0076] In specific embodiments of the present invention, tin accounts for 8 wt% to 15 wt% of the tin / hard carbon composite material. Further, the tin content varies, ranging from 8 wt%, 10 wt%, 12 wt%, 14 wt%, to 15 wt%. The tin loading can be adjusted according to actual needs. Insufficient tin loading results in low specific capacity of the material; excessive tin loading leads to low cycle performance and low first-time efficiency.
[0077] Embodiments of the present invention also provide a negative electrode sheet comprising the aforementioned tin / hard carbon composite material.
[0078] In a specific embodiment of the present invention, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side of the current collector. The negative active material layer is obtained by coating the current collector with a negative electrode slurry, drying, and then rolling. The negative electrode slurry includes a negative electrode material (the aforementioned tin / hard carbon composite material), a conductive agent, a binder, and a solvent. The current collector can be selected as copper foil, and the proportions of the conductive agent and the binder are each less than or equal to 5%. The conductive agent can be selected as carbon black, carbon nanotubes, graphene, etc., the binder can be selected as styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), etc., and the solvent can be selected as deionized water.
[0079] In a specific embodiment of the present invention, when preparing the negative electrode sheet, the raw materials are first weighed, and the negative electrode material, conductive agent (SP), and binder (CMC) are mixed in a mass ratio of 90:5:5. This mixture is then dissolved in a certain amount of deionized water, stirred evenly, coated onto the negative electrode current collector, and dried, rolled, and cut to obtain the negative electrode sheet. The present invention does not impose any special limitations on the preparation process of the negative electrode sheet; any preparation method known to those skilled in the art is acceptable.
[0080] An embodiment of the present invention also provides a secondary battery comprising the aforementioned negative electrode sheet.
[0081] The present invention does not impose any special limitations on the preparation method of the battery; any battery preparation method known to those skilled in the art is acceptable.
[0082] To further understand the present invention, the sodium ion modified layered oxide cathode material, its preparation method, and its application provided by the present invention will be described in detail below with reference to specific embodiments and comparative examples. The scope of protection of the present invention is not limited by the following embodiments.
[0083] Example 1
[0084] (1) 1.29 g aminophenol, 1.3 mL formaldehyde solution (concentration 1.09 g / mL), 0.1 g stannous chloride and 3 mL ammonia solution (concentration 13.3 mol / L) were poured into 50 mL deionized water to form a mixed solution. After reacting at room temperature for 1 hour, acetone solution was added to repeatedly remove the soluble part. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried in an oven at 80 degrees Celsius.
[0085] (2) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 6 hours at a heating rate of 5 degrees Celsius per minute. The product was named Sn / HCS.
[0086] (3) Take 1g of the above Sn / HCS material, 1.29g of aminophenol, 1.3mL of formaldehyde solution (concentration 1.09g / mL), 0.1g of stannous chloride and 3mL of ammonia solution (concentration 13.3mol / L) and pour them into 50mL of deionized water to form a mixed solution. After reacting at room temperature for 1 hour, add acetone solution to repeatedly remove the soluble part. Collect the precipitate and wash it repeatedly with deionized water and anhydrous ethanol, and then dry it in an oven at 80 degrees Celsius.
[0087] (4) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 6 hours at a heating rate of 5 degrees Celsius per minute to obtain a multi-shell single-atom Sn / HCS hollow spherical sodium-ion battery anode composite material.
[0088] Characterization of multi-shell single-atom Sn / HCS hollow spherical sodium-ion battery anode composite material as follows: Figure 1 As shown, from Figure 1 It can be seen that the prepared sodium-ion battery anode composite material exhibits a hollow sphere nested structure.
[0089] Example 2
[0090] (1) 1.1 g aminophenol, 1.2 mL formaldehyde solution (concentration 1.09 g / mL), 0.08 g stannous chloride and 3 mL ammonia solution (concentration 13.3 mol / L) were poured into 50 mL deionized water to form a mixed solution. After reacting at room temperature for 1 hour, acetone solution was added to repeatedly remove the soluble part. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried in an oven at 80 degrees Celsius.
[0091] (2) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute. The resulting product was named Sn / HCS.
[0092] (3) Take 1g of the above Sn / HCS material, add 1.1g of aminophenol, 1.2mL of formaldehyde solution (concentration 1.09g / mL), 0.08g of stannous chloride and 3mL of ammonia solution (concentration 13.3mol / L) to 50mL of deionized water to form a mixed solution. After reacting at room temperature for 1 hour, add acetone solution to repeatedly remove the soluble part. Collect the precipitate and wash it repeatedly with deionized water and anhydrous ethanol, and then dry it in an oven at 80 degrees Celsius.
[0093] (4) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute to obtain a multi-shell single-atom Sn / HCS hollow spherical sodium-ion battery anode composite material.
[0094] Example 3
[0095] (1) 1.2 g aminophenol, 1.2 mL formaldehyde solution (concentration 1.09 g / mL), 0.09 g stannous chloride and 3 mL ammonia solution (concentration 13.3 mol / L) were poured into 50 mL deionized water to form a mixed solution. After reacting at room temperature for 1 hour, acetone solution was added to repeatedly remove the soluble part. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried in an oven at 80 degrees Celsius.
[0096] (2) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 700 degrees Celsius for 7 hours at a heating rate of 5 degrees Celsius per minute. The product was named Sn / HCS.
[0097] (3) Take 1g of the above Sn / HCS material, add 1.2g of aminophenol, 1.2mL of formaldehyde solution (concentration 1.09g / mL), 0.09g of stannous chloride and 3mL of ammonia solution (concentration 13.3mol / L) to 50mL of deionized water to form a mixed solution. After reacting at room temperature for 1 hour, add acetone solution to repeatedly remove the soluble part. Collect the precipitate and wash it repeatedly with deionized water and anhydrous ethanol, then dry it in an oven at 80 degrees Celsius.
[0098] (4) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 700 degrees Celsius for 7 hours at a heating rate of 5 degrees Celsius per minute to obtain a multi-shell single-atom Sn / HCS hollow spherical sodium-ion battery anode composite material.
[0099] Example 4
[0100] (1) 1.1 g aminophenol, 1.1 mL formaldehyde solution, 0.1 g stannous chloride (concentration 1.09 g / mL) and 3 mL ammonia solution (concentration 13.3 mol / L) were poured into 50 mL deionized water to form a mixed solution. After reacting at room temperature for 1 hour, acetone solution was added to repeatedly remove the soluble part. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried in an oven at 80 degrees Celsius.
[0101] (2) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute. The resulting product was named Sn / HCS.
[0102] (3) Take 1g of the above Sn / HCS material, add 1.1g of aminophenol, 1.1mL of formaldehyde solution (concentration 1.09g / mL), 0.1g of stannous chloride and 3mL of ammonia solution (concentration 13.3mol / L) to 50mL of deionized water to form a mixed solution. After reacting at room temperature for 1 hour, add acetone solution to repeatedly remove the soluble part. Collect the precipitate and wash it repeatedly with deionized water and anhydrous ethanol, then dry it overnight in an oven at 80 degrees Celsius.
[0103] (4) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute to obtain a multi-shell single-atom Sn / HCS hollow spherical sodium-ion battery anode composite material.
[0104] Example 5
[0105] (1) 1.1 g aminophenol, 1.1 mL formaldehyde solution (concentration 1.09 g / mL), 0.01 g stannous chloride and 3 mL ammonia solution (concentration 13.3 mol / L) were poured into 50 mL deionized water to form a mixed solution. After reacting at room temperature for 1 hour, acetone solution was added to repeatedly remove the soluble part. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried in an oven at 80 degrees Celsius.
[0106] (2) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute. The resulting product was named Sn / HCS.
[0107] (3) Take 1g of the above Sn / HCS material, add 1.1g of aminophenol, 1.1mL of formaldehyde solution (concentration 1.09g / mL), 0.01g of stannous chloride and 3mL of ammonia solution (concentration 13.3mol / L) to 50mL of deionized water to form a mixed solution. After reacting at room temperature for 1 hour, add acetone solution to repeatedly remove the soluble part. Collect the precipitate and wash it repeatedly with deionized water and anhydrous ethanol, then dry it in an oven at 80 degrees Celsius.
[0108] (4) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute to obtain a multi-shell hollow spherical sodium-ion battery anode composite material with a very small amount of single-atom Sn / HCS loading.
[0109] Comparative Example 1
[0110] (1) In this comparative example, commercial tin powder was directly used as the negative electrode material of sodium-ion battery.
[0111] Comparative Example 2
[0112] (1) 1.1 g aminophenol, 1.1 mL formaldehyde solution (concentration 1.09 g / mL) and 3 mL ammonia solution (concentration 13.3 mol / L) were poured into 50 mL deionized water to form a mixed solution. After reacting at room temperature for 1 hour, acetone solution was added to repeatedly remove the soluble part. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried in an oven at 80 degrees Celsius.
[0113] (2) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute. The resulting product was named HCS.
[0114] (3) Pour 1.1 g of aminophenol, 1.1 mL of formaldehyde solution (concentration 1.09 g / mL), and 3 mL of ammonia solution (concentration 13.3 mol / L) into 50 mL of deionized water to form a mixed solution. After reacting at room temperature for 1 hour, add acetone solution to repeatedly remove the soluble part. Collect the precipitate and wash it repeatedly with deionized water and anhydrous ethanol, then dry it in an oven at 80 degrees Celsius.
[0115] (4) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute to obtain the MHCS sodium ion battery anode composite material.
[0116] Comparative Example 3
[0117] (1) 1.1 g aminophenol, 1.1 mL formaldehyde solution (concentration 1.09 g / mL), 0.06 g tin oxide and 3 mL ammonia solution (concentration 13.3 mol / L) were poured into 50 mL deionized water to form a mixed solution. After reacting at room temperature for 1 hour, acetone solution was added to repeatedly remove the soluble part. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried in an oven at 80 degrees Celsius.
[0118] (2) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute. The product was named SnO2@HCS.
[0119] (3) The above materials SnO2@HCS, 1.1g aminophenol, 1.1mL formaldehyde solution (concentration 1.09g / mL) and 3mL ammonia solution (concentration 13.3mol / L) were poured into 50mL deionized water to form a mixed solution. After reacting at room temperature for 1 hour, acetone solution was added to repeatedly remove the soluble part. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried in an oven at 80 degrees Celsius.
[0120] (4) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute to obtain SnO2@HCS sodium ion battery anode composite material.
[0121] Comparative Example 4
[0122] (1) 1.1 g aminophenol, 1.1 mL formaldehyde solution (concentration 1.09 g / mL), 0.1 g stannous chloride and 3 mL ammonia solution (concentration 13.3 mol / L) were poured into 50 mL deionized water to form a mixed solution, and reacted at room temperature for 1 hour. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried in an oven at 80 degrees Celsius.
[0123] (2) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute to obtain the Sn / CS sodium ion battery anode composite material.
[0124] Comparative Example 5
[0125] (1) 1.1 g aminophenol, 1.1 mL formaldehyde solution (concentration 1.09 g / mL), 0.1 g stannous chloride and 3 mL ammonia solution (concentration 13.3 mol / L) were poured into 50 mL deionized water to form a mixed solution. After reacting at room temperature for 1 hour, acetone solution was added to repeatedly remove the soluble part. The precipitate was collected and washed repeatedly with deionized water and anhydrous ethanol, and then dried overnight in an oven at 80 degrees Celsius.
[0126] (2) The dried material was placed in a tube furnace under a nitrogen atmosphere for high-temperature calcination at 600 degrees Celsius for 8 hours at a heating rate of 5 degrees Celsius per minute to obtain the Sn / HCS sodium ion battery anode composite material.
[0127] Battery assembly and performance testing methods:
[0128] (1) Battery assembly: The negative electrode was made using the materials prepared in Examples 1-5 and Comparative Examples 1-5 as the negative electrode active material, and the positive electrode was made using a sodium metal sheet. The electrolyte was 1.0 mol / L NaPF6 dissolved in diethylene glycol dimethyl ether. The batteries were assembled into CR2032 button batteries in an argon glove box.
[0129] (2) Performance testing methods: The Land battery testing system was used to test the GCD within a voltage window of 0.01–2V. Constant current charge-discharge tests were performed at a current density of 50 mA / g, with a voltage range of 0–2V, and the initial charge-discharge capacity and initial coulombic efficiency were recorded. Constant current charge-discharge tests were then performed at a current density of 500 mA / g, with a voltage range of 0–2V. After 500 cycles, the discharge capacity was recorded, and the capacity retention rate was calculated using the formula. The electrochemical performance test results of the coin cells assembled from the materials obtained in Examples 1–5 and Comparative Examples 1–5 are shown in Table 1.
[0130] Table 1. Electrochemical performance test results of coin cells assembled from the materials obtained in Examples 1-5 and Comparative Examples 1-5.
[0131]
[0132] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A tin / hard carbon composite material, characterized in that, The tin / hard carbon composite material is a nested structure of several hollow spheres, with the hollow spheres consisting of single-atom tin distributed on the carbon skeleton of the hollow carbon spheres; The preparation method of the tin / hard carbon composite material includes the following steps: (1) Mix aminophenol, formaldehyde solution, alkaline catalyst and tin salt solution evenly, react to obtain the first mixed solution, add acetone solution to dissolve the soluble matter, filter and dry to obtain tin-loaded hard carbon precursor; (2) Under an inert gas atmosphere, the tin-loaded hard carbon precursor was calcined to obtain hollow carbon spheres loaded with tin atoms. (3) Preparation of tin-loaded hard carbon precursor on hollow carbon spheres loaded with tin atoms: Take hollow carbon spheres loaded with tin atoms, aminophenol, formaldehyde solution, alkaline catalyst and tin salt solution, mix them evenly, react to obtain a second mixed solution, add acetone solution to dissolve the soluble matter, filter and dry to obtain the product; (4) The product is calcined in an inert gas atmosphere to obtain the tin / hard carbon composite material; In steps (1) and (3), the mass ratio of aminophenol to tin salt in the tin salt solution is 1.1~1.3:0.05~0.
15.
2. The tin / hard carbon composite material according to claim 1, characterized in that, Single-atom tin is bonded to hollow carbon spheres by Sn-C bonds.
3. The tin / hard carbon composite material according to claim 1, characterized in that, Tin accounts for 8 wt% to 15 wt% of tin / hard carbon composite materials.
4. A method for preparing the tin / hard carbon composite material as described in any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Mix aminophenol, formaldehyde solution, alkaline catalyst and tin salt solution evenly, react to obtain the first mixed solution, add acetone solution to dissolve the soluble matter, filter and dry to obtain tin-loaded hard carbon precursor; (2) Under an inert gas atmosphere, the tin-loaded hard carbon precursor was calcined to obtain hollow carbon spheres loaded with tin atoms. (3) Preparation of tin-loaded hard carbon precursor on hollow carbon spheres loaded with tin atoms: Take hollow carbon spheres loaded with tin atoms, aminophenol, formaldehyde solution, alkaline catalyst and tin salt solution, mix them evenly, react to obtain a second mixed solution, add acetone solution to dissolve the soluble matter, filter and dry to obtain the product; (4) The product is calcined in an inert gas atmosphere to obtain the tin / hard carbon composite material.
5. The preparation method according to claim 4, characterized in that, In steps (1) and (3), at least one of the following features ① to ⑦ must be satisfied: ①The aminophenol is independently selected from one or more of o-aminophenol, m-aminophenol, and p-aminophenol; ② The concentration of the formaldehyde solution is 1~1.1g / mL; ③ The molar ratio of aminophenol to formaldehyde is 1:2 to 1:4; ④ The alkaline catalyst is an ammonia solution with a concentration of 10-15 mol / L; the volume ratio of the ammonia solution to the tin salt solution is 3-5:
50. ⑤ The tin salt in the tin salt solution is independently selected from one or more of stannous chloride, stannous fluoride, and stannous iodide, and the concentration of the tin salt solution is 0.05~0.1mol / L; ⑥ The mass ratio of the aminophenol to the tin salt in the tin salt solution is 1.1~1.3:0.05~0.15; ⑦ The volume ratio of water to acetone in the acetone solution is 1:
1.
6. The preparation method according to claim 4, characterized in that, In step (3), the volume-to-mass ratio of the tin salt solution to the hollow carbon sphere loaded with uniatomic tin is 50 ml: 1~5 g.
7. The preparation method according to claim 4, characterized in that, In steps (1) and (3), the reaction is carried out at room temperature for 0.5 to 1 hour. The drying temperature is 70~80℃.
8. The preparation method according to claim 4, characterized in that, In steps (2) and (4), the inert gas is independently selected from one or more of nitrogen, argon, and helium; the heating rate of the calcination treatment is 0.5~5℃ / min, the temperature is 600~800℃, and the time is 6~8h.
9. A negative electrode sheet, characterized in that, Includes the tin / hard carbon composite material as described in any one of claims 1 to 3.
10. A secondary battery, characterized in that, Includes the negative electrode sheet as described in claim 9.
Citation Information
Patent Citations
Sodium-ion battery negative electrode tin-carbon composite hollow sphere material and application thereof
CN108376774A
Multilayer porous hollow bowl-shaped carbon material and preparation method thereof
CN110171812A